Emerging Challenges of Preclinical Models of Anti-tumor Immunotherapeutic Strategies Utilizing Vγ9Vδ2 T Cells - Joalland, Noémie; Scotet, Emmanuel (Frontiers in Immunology, 2020)
Despite recent advances, the eradication of cancers still represents a challenge which justifies the exploration of additional therapeutic strategies such as immunotherapies, including adoptive cell transfers. Human peripheral Vγ9Vδ2 T cells, which constitute a major transitional immunity lymphocyte subset, represent attractive candidates because of their broad and efficient anti-tumor functions, as well as their lack of alloreactivity and easy handling. Vγ9Vδ2 T cells act like immune cell stress sensors that can, in a tightly controlled manner but through yet incompletely understood mechanisms, detect subtle changes of levels of phosphorylated metabolites of isoprenoid synthesis pathways. Consequently, various anti-tumor immunotherapeutic strategies have been proposed to enhance their reactivity and cytotoxicity, as well as to reduce the deleterious events. In this review, we expose these advances based on different strategies and their validation in preclinical models. Importantly, we next discuss advantages and limits of each approach, by highlighting the importance of the use of relevant preclinical model for evaluation of safety and efficacy. Finally, we propose novel perspectives and strategies that should be explored using these models for therapeutic improvements.